Heavy metal tolerance and biosorption ability of a fresh water prawn probiotic, bacillus cereus strain BP-MBRG/1b - Ong, Chin Yong; Wan Johari, Wan Lutfi; Mohd Ikhsan, Natrah Fatin; Ahmad, Siti Aqlima; Yasid, Nur Adeela; Shukor, Mohd Yunus (E M International, 2019)
Heavy metal pollution in fresh water is a serious environmental problem, as it possesses toxicity effects to the aquaculture organisms. The use of probiotics can be a method to remove heavy metals in the environment effectively and economically. The objectives of this research are to measure the growth rate of the fresh water prawn probiotic (Bacillus cereusstrain BP-MBRG/1b) under the effects of different concentrations of selected heavy metal (Cr, Zn, Cu, Cd, Ni, Al, Fe, Mg) and the bioremoval ability towards selected heavy metal (Cd, Cu, Cr, Fe). Bacterial strains were grown in nutrient broth with the addition 5ppm and 10 ppm of selected heavy metal at 37 oC for 7 hours to determine the growth under exposure to heavy metals. Cr, Cu, Ni and Mgat 5 ppm completely inhibited the growth while the others (Cd, Zn, Fe, Al) partially inhibit the growth with inhibition percentage of 33.95%, 40.12%, 41.47% and 75.03% respectively. All the tested heavy metals with 10 ppm concentration completely inhibited the growth of the strain. The bioremediation experiment was conducting by exposing the wet biomass of the strain to 5ppm heavy metals solution for 2 hours. The concentrations of heavy metals were then measured using Atomic Absorption Spectrometry (AAS). The strain had the highest removal efficiency on the Fe (15.43%, 0.322 mg/g), followed by Cr (6.90%, 0.135mg/g), Cu (2.34%, 0.026mg/g), and Cd (0.82%, 0.009 mg/g).